Israeli Mediterranean vermetid reef biodiversity monitoring data - Rilov, Gil (PANGAEA, 2019)
Data presented are percent cover or count averages of 15 quadrats randomly placed along a 50 meter transect placed parallel to the shoreline at one of four intertidal zones at several vermetid reef sites along the Israeli coast in surveys conducted between fall 2009 to winter 2017. Four sites were surveyed seasonally and 7 more, annually. Taxa include macroalgae and macro-invertebrates. Details: The surveyed taxa were identified to the lowest taxonomic level attainable in the field (mostly genus or species level but in several cases family, order or general taxonomic /functional group, e.g., limpets). The macroalgae forming a matrix of low-lying mats (usually < 1 cm in height) were referred to as turf. Mean taxa abundance was quantified at the study sites using the transect-quadrat method. Percent cover of sessile taxa and the density of mobile macrofauna were counted in a 0.25 m2 (50 × 50 cm) quadrat (divided into 100, 5 × 5 cm, sub-squares). The quadrat was placed haphazardly along a 50 m transect laid parallel to the water edge at each shore level/zone (n= 15 quadrats per transect). To ensure resampling on the exact transect position, the ends of the line transects were marked with stainless-steel bolts. The vermetid reef was divided into four zones. Two were on the platform flat itself, which is found at the low-shore level: one was at the platform seaward 'edge' zone, the area where a rim formed by the vermetid Dendropoma anguliferum still exists in some sites, and the platform flat 'center', normally two to three meters inwards from the edge. The center in most sites is characterized by a shallow basin (5-10 cm deep) that normally holds water during low tide and calm sea conditions. In the event that a quadrat was haphazardly placed on deep plot of reef (i.e. in a tidepool or pothole) it was repositioned, as these deeper sections mostly represent a subtidal, and where (under normal sea conditions) benthic cover is difficult to assess. The other two zones represent different heights along the mid-shore level at the back of the platform which varied among sites in its degree of slope angle. The 'Mid-mid' zone, is located several centimeters above the platform flat and out of the water during calm conditions even when water is held by the platform during low tide, and the 'High-mid' zone, ~20-30 cm above the Mid-mid zone.